Proposal Decision Support Process for Urban Goods Delivery - Atik El Ftouh, Mouna; Azmani, Abdellah; Fourka, Mohamed (International Journal of Supply Chain Management, 2019)
This paper proposes a collaborative process to handle demands received by a carrier for urban goods delivery.The purpose of this article is to provide support for carriers analyzing the demands,physical resources,human resources,risks and profitability,in order to decide processing internally or externally a goods delivery demand or rejecting it.Such a process,called CUFP(Collaborative Urban Freight Process),is based on an analysis of urban movements of goods,divided into four stages:Check out of extreme conditions,feasibility study,exploitation study and execution.